Application of Play Therapy to Children's Anxiety Level Due to Hospitalization - Ni Luh Emilia; Juana Eunike Putri Saito; Denny Susanto; Juliana Neng Ribka Sarman; Sabarulin Sabarulin (An Idea Health Journal, 2024)
Hospitalization occurs because the child is sick, which can cause fear and anxiety problems. The need for treatment due to anxiety, one of which is providing play therapy. Play therapy is a structured game, which is implemented by nurses with the aim of reducing anxiety due to hospitalization. The method used is a descriptive case study with 2 respondents who experience anxiety. The level of anxiety was measured in pre-post therapy using the QUESTT questionnaire which contained an anxiety scale, namely the Facial Anxiety Scale (FAS) and Visual Facial Anxiety Scale (VFAS), followed by providing play therapy coloring pictures for 3 consecutive days within 30 minutes. The result of applying play therapy to both respondents was the disappearance of anxiety. In child F with the pre-play therapy FAS anxiety scale, a score of 3 was obtained and post-therapy a score of 0, while the VFAS pre-play therapy obtained a score of A4 and after play therapy, a score of A0 was obtained, likewise for child G, the anxiety level with the pre-play therapy FAS scale was obtained with a score of 1 and The play therapy port got a score of 0, while the pre-play therapy VFAS got a score of A2 and post play therapy got a score of A0. Play therapy is effective in reducing or even reducing anxiety in children due to hospitalization. It is hoped that nursing staff will be able to apply play therapy to nursing care in overcoming anxiety problems due to hospitalization in children.